Interpretasi Visual terhadap Bentuk dan Fungsi Kujang Huma Pamangkas dengan Uji ANOVA (Analysis Of Variance) dan VAS (Visual Analog Scale) - Putra, Edi Setiadi (Jurnal Rekarupa, 2011)
Abstract   The kujang recognizable as a typical cultural artifact Sunda. Classification of Kujang is determined by functions, namely as weapons, agricultural tools and ceremonial tool. The functions of kujangs are determined based on user behavior that characterize a particular form, this phenomenon is interesting to traced, to determine the elements in form of Kujang huma pamangkas as agricultural tools who showing variability of functions, the study sought to explore the visual perception of some observers, through VAS approach (visual analog scale) and the ANOVA test (analysis of variance), towards some form of kujang pamangkas from several museums, This study concluded the fact the relationship between form with function (form follows function), which was preserved until the present into the design characteristics of traditional farming tools in west Java. Keyword: Kujang, huma, Sunda ABSTRAK   Kujang dikenali sebagai artefak khas budaya Sunda. Klasifikasi kujang ditentukan berdasarkan fungsinya, yaitu sebagai senjata, perkakas pertanian serta alat upacara. Fungsi-fungsi kujang ditentukan berdasarkan perilaku pengguna yang membentuk karakter bentuk tertentu. Fenomena ini menarik untuk ditelusuri, guna mengetahui unsur pada karakter bentuk kujang perkakas pertanian yaitu kujang huma pamangkas yang menunjukkan variabilitas fungsi. Penelitian ini mencoba menggali persepsi visual dari beberapa pemerhati, melalui pendekatan VAS (Visual Analog Scale) dan uji ANOVA (Analysis Of Variance), terhadap beberapa bentuk artefak kujang pamangkas dari beberapa museum. Penelitian ini menyimpulkan adanya fakta keterkaitan antara bentuk dengan fungsinya (form follows function), yang dilestarikan hingga masa kini kedalam karakter desain perkakas pertanian tradisional di Jawa Barat.   Kata kunci: Kujang, huma, Sunda